(untitled) (Journal of Health Sciences, 2025)
Introduction: Musculoskeletal disorders (MSDs) are among the leading causes of disability worldwide, often resulting in pain, loss of function, and reduced quality of life. Kinesio Taping (KT) has been proposed as a supportive, noninvasive technique to enhance rehabilitation outcomes by improving neuromuscular activation, proprioception, and circulation. This research aims to evaluate the effect of KT on upper-limb functional improvement in patients with MSDs undergoing standard physiotherapy. Methods: This prospective interventional study included 57 participants divided into a control group receiving conventional physiotherapy and an experimental group receiving additional KT. Functional status was assessed using the Upper Extremity Functional Index (UEFI) at 3 time points: before therapy, mid-treatment, and after therapy. Statistical analyses included the Mann–Whitney U test, Kruskal–Wallis test, and multiple linear regression. Results: At baseline, the KT group had significantly lower functional scores (median 24.0, Interquartile Range [IQR] 19.0–27.0) than controls (median 35.0, IQR 25.0–47.0; p = 0.02). During treatment, both groups improved, but the KT group demonstrated faster functional recovery (p = 0.033). At completion, both groups achieved similar UEFI scores; however, the total functional gain was nearly twice as high in the KT group (21.5 vs. 12.5 points). Relative improvement reached 90% in the KT group compared with 36% in controls. Regression analysis confirmed that KT application was a significant predictor of upper-limb functional improvement (β = 0.552, p = 0.002). Conclusion: KT significantly accelerates upper-limb functional recovery and enhances rehabilitation outcomes when used as an adjunct to physiotherapy. Its simplicity, safety, and cost-effectiveness make it a valuable addition to standard musculoskeletal rehabilitation.